A systematic review and quantitative synthesis of the long-term psychiatric sequelae of pediatric autoimmune encephalitis - Nguyen, Linda; Yang, Jennifer H.; Goyal, Sajan; Irani, Najin; Graves, Jennifer S. (Journal of affective disorders, 2022)
Long-term neuropsychiatric sequelae of autoimmune encephalitis (AE) remain understudied, particularly in pediatric-onset AE. We aimed to synthesize the published data on ongoing psychiatric symptoms in pediatric-onset AE. The Pubmed, PyscINFO, Web of Science databases were searched from their inception years to August 23, 2021, and 29 studies were identified and analyzed. We also performed a quantitative synthesis of available patient data from the 29 studies combined with a cohort of anti-NMDA receptor (NMDAR) AE from our institution to examine the associations between acute treatment course and long-term psychiatric outcome. At long-term follow up, 52.4% of the cases with pediatric-onset AE had any persistent symptom and 36.0% had at least one psychiatric symptom. Pooled data found that 36.3% of pediatric-onset anti-NMDAR AE had ongoing psychiatric symptoms. Using a univariate logistic regression analysis, we found that abnormal initial EEG, use of certain immunotherapies, and persistent cognitive impairments were associated with ongoing psychiatric symptoms. Limitations of the existing literature included a significant paucity of outcomes measured using consistent, objective methods. Limitations of the systematic review included the wide variability among the studies reviewed, which rendered a meta-analysis impossible and beyond the scope of the paper. Chronic psychiatric and behavioral problems remain present in one-third of children months to years after onset of AE. Larger scaled prospective observational studies with a consistent standardized battery of testing are needed to examine impact of specific clinical features and immunotherapies on long-term mental health outcomes. •There is very little data on long-term psychiatric outcome data for pediatric-onset autoimmune encephalitis (AE).•A total of 29 studies were analyzed in the systematic review, and study quality was mostly low to medium.•One-third of children with AE have long-term psychiatric symptoms.•Longitudinal psychiatric testing and care are essential to the management of patients with AE.